Role of Higenamine in Heart Diseases: A Mini-Review - Wen, Jianxia; Li, Mingjie; Zhang, Wenwen; Wang, Haoyu; Bai, Yan; Hao, Junjie; Liu, Chuan; Deng, Ke; Zhao, Yanling (Frontiers in Pharmacology, 2022)
Higenamine, a natural product with multiple targets in heart diseases, is originally derived from Aconitum, which has been traditionally used in China for the treatment of heart disease, including heart failure, arrhythmia, bradycardia, cardiac ischemia/reperfusion injury, cardiac fibrosis, etc. This study is aimed to clarify the role of higenamine in heart diseases. Higenamine has effects on improving energy metabolism of cardiomyocytes, anti-cardiac fibroblast activation, anti-oxidative stress and anti-apoptosis. Accumulating evidence from various studies has shown that higenamine exerts a wide range of cardiovascular pharmacological effects in vivo and in vitro, including alleviating heart failure, reducing cardiac ischemia/reperfusion injury, attenuating pathological cardiac fibrosis and dysfunction. In addition, several clinical studies have reported that higenamine could continuously increase the heart rate levels of healthy volunteers as well as patients with heart disease, but there are variable effects on systolic blood pressure and diastolic blood pressure. Moreover, the heart protection and therapeutic effects of higenamine on heart disease are related to regulating LKB1/AMPKα/Sirt1, mediating the β2-AR/PI3K/AKT cascade, induction of heme oxygenase-1, suppressing TGF-β1/Smad signaling, and targeting ASK1/MAPK (ERK, P38)/NF-kB signaling pathway. However, the interventional effects of higenamine on heart disease and its underlying mechanisms based on experimental studies have not yet been systematically reviewed. This paper reviewed the potential pharmacological mechanisms of higenamine on the prevention, treatment, and diagnosis of heart disease and clarified its clinical applications. The literature shows that higenamine may have a potent effect on complex heart diseases, and proves the profound medicinal value of higenamine in heart disease.